2015
DOI: 10.1021/ic502873d
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Tri- and Dimetallic Pyridine Dicarboxamide Cryptates: Unusual O,N,O-Coordination and Facile Access to Secondary Coordination Sphere Hydrogen Bonding Interactions

Abstract: A series of tri- and dimetallic metal complexes of pyridine dicarboxamide cryptates are reported in which changes to the base and metal source result in diverse structure types. Addition of strong bases, such as KH or KN(SiMe3)2, followed by divalent metal halides allows direct access to trinuclear complexes in which each metal center is coordinated by a dianionic N,N,N-chelate of each arm. These complexes bind a guest K(+) cation within the central cavity in a trigonal planar coordination environment. Minor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 140 publications
1
8
0
Order By: Relevance
“…Unlike the hydrocarbon oxidation reactions, the Ph 3 P reactions were followed by 1 H NMR. As has been found for other systems, the catalyst-free reaction between PhIO and Ph 3 P did not yield any Ph 3 PO …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Unlike the hydrocarbon oxidation reactions, the Ph 3 P reactions were followed by 1 H NMR. As has been found for other systems, the catalyst-free reaction between PhIO and Ph 3 P did not yield any Ph 3 PO …”
Section: Resultssupporting
confidence: 80%
“…As has been found for other systems, the catalyst-free reaction between PhIO and Ph 3 P did not yield any Ph 3 PO. 64…”
Section: ■ Resultsmentioning
confidence: 99%
“…This conclusion was supported by EPR analysis of the oxygenated complexes, which showed the signal for a mononuclear Cu­(II) center and the remaining two Cu­(II) centers linked by hydroxo groups. Magnetic studies revealed a ferromagnetically coupled Cu­(II)­Cu­(II) center along with an isolated Cu­(II) in these complexes . Although these tricopper complexes do not typically support hydrocarbon oxidation, they represent a popular approach to the problem, and ligand-assisted formation of trinuclear complexes has been reported for other metal ions such as manganese, iron, cobalt, and zinc, as well. …”
Section: Toward the Development Of A Biomimetic Catalystmentioning
confidence: 86%
“…Previously, well-defined polynuclear clusters could be obtained from dimensional reduction of 3D-lattices. Unfortunately, examples of dimensional reduction are limited in number, and to date, most current cluster syntheses rely on self-assembly reactions that lack control of the resulting cluster constitution, geometry, and local metal coordination environments. Thus, reliable methods to assemble polynuclear clusters are required to rigorously undertake electronic structure evaluation of mixed valent clusters. Our lab and others have reported the synthesis of clusters with varying nuclearity (three metals and higher) templated within a polynucleating ligand architecture to predispose the metal ions to bind in a specific manner to form the polynuclear aggregate. The resulting clusters have been utilized to explore the nature of the metal–metal interactions by varying auxiliary ligand coordination to the polynuclear system, analyzing the effect of distance between the metals to develop magneto-structural correlations, and assessing electronic structure perturbations as a function of cluster redox level. …”
Section: Introductionmentioning
confidence: 99%